THE ROLE OF THE COMMUNITY AND THE VILLAGE GOVERNMENT IN UTILIZING THE POTENTIAL OF THE VILLAGE IN THE TANAH PUTIH VILLAGE, BOTUPINGGE DISTRICT, BONE BOLANGO REGENCY - Sahran Tobuhu; Titin Dunggio; Ely Ibrahim (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This study aims to determine the role of the government in exploring thepotential that exists in Tanah Putih Village, Botupingge District and the role of thecommunity in exploiting the potential to increase people's income in Tanah PutihVillage, Botupingge District.The method in this study uses qualitative research methods with primary andsecondary data sources with data collection techniques by means of observation,interviews and documentation.Based on the research results, it can be concluded that (1) the role of the villagegovernment and village institutions is very influential in exploring the potential thatexists in the village (2) the community must be able to process the existing potentialso as to increase their income.